EXPLORING THE CONNECTION BETWEEN SECOND LANGUAGE VOCABULARY LEARNING STRATEGIES AND VOCABULARY KNOWLEDGE - Denitza A. Charkova; Krassimira Charkova (Informascope, 2018)
The present study sought to explore and identify vocabulary learning strategies that lead to the attainment of depth of vocabulary knowledge in a second language. For the purpose, 110 Bulgarian language learners of English took Qian and Schedl's (2004) depth of vocabulary knowledge test and completed a related survey. After dividing the sample into a limited knowledge group and a superior knowledge group, the data were analyzed through discriminant function analysis which showed eight vocabulary learning strategies as significantly associated with the superior knowledge group. These strategies were named linguistically-driven strategies since they involve regular attention to linguistic features, including: paradigmatic associations (synonyms, antonyms), morphological structure (prefixes, roots, and suffixes), syntagmatic associations (collocations) and pronunciation. The results suggest that regular use of linguistically-driven vocabulary learning strategies helps build deep knowledge of second language vocabulary.